2020
DOI: 10.29252/rbmb.9.1.89
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Carbon Nanotubes Containing an Anti-Bacterial Chemical Component and its Effect on MDR and XDR Isolates of Pseudomonas Aeruginosa

Abstract: Background: Pseudomonas aeruginosa is an opportunistic human pathogen that causes severe acute and chronic nosocomial infections, especially in immunocompromised burn patients. and can lead to severe mortality and morbidity. The emergence of antibiotic resistant P. aeruginosa infections has created significant challenges in treating these patients. A potential alternative treatment for antibiotic resistant pathogens includes the use of carbon nanotubes (CNTs), which have received considerable attention due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This may have different consequences on the outcome of infection (42). So, our result revealed that the isolate has high virulence mechanism to deliver the effector proteins affecting host cells and other bacteria in their milieu (43)(44)(45).…”
Section: Isolates Possessmentioning
confidence: 86%
“…This may have different consequences on the outcome of infection (42). So, our result revealed that the isolate has high virulence mechanism to deliver the effector proteins affecting host cells and other bacteria in their milieu (43)(44)(45).…”
Section: Isolates Possessmentioning
confidence: 86%
“…Banihashemi et al in 2020 investigated the antibacterial properties of this same chemical compounds coated onto the same carbon nanotubes on 30 burned Wistar mice which were artificially infected with Pseudomonas aeruginosa . They concluded that simultaneous treatment of the compound and nanotubes was highly effective for treatment ( 37 ). Limitation of the current study was that we have not yet tested the chemical compound directly on human burn wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers created Ag@CNT/PA composite nanobers by combining polyamide (PA), CNTs, and Ag NPs, which exhibited remarkable antibacterial properties and effectively combated drug resistance. 202 The typical 2D carbon materials including graphene and MXene have also demonstrated good antibacterial activity. Graphene has garnered extensive attention due to its high antibacterial activity with little resistance and high biocompatibility, which is an ideal carrier for antibacterial substances.…”
Section: Nanobactericides Against Mdr Bacteriamentioning
confidence: 99%
“…Researchers created Ag@CNT/PA composite nanofibers by combining polyamide (PA), CNTs, and Ag NPs, which exhibited remarkable antibacterial properties and effectively combated drug resistance. 202…”
Section: Nanobactericides Against Mdr Bacteriamentioning
confidence: 99%